Assessment of Cytological Changes of Oral Mucosal in Smokers - Refangga Sudi Wardana; Humairah Medina Liza Lubis (HM Publisher, 2023)
Tobacco use, both smoking, and chewing, is a risk factor for the development of oral mucosa changes. Tobacco in cigarettes causes an imbalance between antioxidant enzymes in metabolizing and detoxifying carcinogens in tobacco, which may cause changes in the oral epithelium that leads to lesions and dysplasia. This study aimed to assess and compare the cytological changes in the oral mucosal of smokers and non-smokers. Assessment of smokers based on the type of cigarette smoking, the degree of smoking, and the duration of smoking. The design study was a case-control study, as was a non-probability sampling method with consecutive sampling obtained from primary sources, including a questionnaire and an examination of epithelial cells under a microscope. The findings revealed that 14 smokers (38. 9%) had changes in oral epithelial cells. The Fisher Exact Test on smoking habits and changes in oral epithelial cells based on the type of cigarette smoked (p=0.001), smoking degree (p=0.000), and duration of smoking (p=0.003) indicated a relationship between smoking-influenced cytological changes in the oral mucosal.